Study of Physical-Chemical Characteristic in Dyeing with Teak Leaf Extract: The Role of Post-Mordant and Alkaline Solution - Cahyaningtyas, Hilmi Amanah Aditya; Vera, Ade; Mulyani, Rr Wiwiek Eka (Universitas Insan Cendekia Mandiri, 2025)
Teak leaf extract has potential as a natural dye for dyeing textile materials because it contains many natural pigments. The exhaust method was used to dye cotton woven fabric with teak leaf extract at 40 oC in an alkaline solution (pH 10). The dyed fabric then proceeded to the postmordant process with a comparison of alum and ferrosulfate variations. Evaluation of physical and chemical characteristics was carried out by testing color fastness and evenness, color space, and color fastness to washing and rubbing. According to the results, ferrosulfate mordant provided the highest values for color fastness and evenness (K/S 1.4805 and SD 0.0055) in comparison to alum (K/S values of 0.2857 and SD 0.0077). Alum mordant created a color space of a* +5.36 and b* +3.75, while ferrosulphate mordant produced a* +0.55 and b* +7.86. Both mordants received good ratings (4-5) for color fastness to washing. Alum had a good color fastness rating (4-5) while ferrosulfate received a rating of (4).